I.YUSUPOV LIRO-EPIKALÍQ POEMALARÍNÍŃ KÓRKEMLEW USÍLLARÍ HÁM ONÍŃ ÁHMIYETI - Ayımbetova, Z.M. (ILIM hám JÁMIYET, 2020)
The article explores the artistic methods used in I. Yusupov’s lyric-epic poems “Watan Topraǵı”, “Mámelek Oy” and “Búlbil Uyasi”. Several types of artistic representation methods were used in these poems, descrebes their importance in creating the artistic expressiveness.